An introduction to the Marburg virus vaccine consortium, MARVAC - Robert W. Cross; Ira M. Longini; Stephan Becker; Karin Bok; David Boucher; Miles W. Carroll; Janet V. Díaz; William E. Dowling; Ruxandra Draghia-Akli; James T. Duworko; John M. Dye; Michael A. Egan; et al. (PLoS Pathogens, 2022)
The emergence of Marburg virus (MARV) in Guinea and Ghana triggered the assembly of the MARV vaccine “MARVAC” consortium representing leaders in the field of vaccine research and development aiming to facilitate a rapid response to this infectious disease threat. Here, we discuss current progress, challenges, and future directions for MARV vaccines.